The Radical Cation of Bithiophene: An Experimental and Theoretical Study. Issue 1 (1999) - Keszthelyi, T.; Grage, M. M.-L.; Wilbrandt, R.; Svendsen, C.; Mortensen, O. S.
Abstract : The electronic absorption spectrum of the bithiophene radical cation prepared by γ -irradiation in a glassy Freon matrix is presented, together with the Raman spectra excited at 550 and 425 nm, in resonance with the two absorption bands. The 425 nm excited Raman spectrum was also recorded in a room temperature acetonitrile solution, in this case the radical cation was generated via a photoinduced electron transfer reaction. The resonance Raman spectra were interpreted with the help of density functional theory calculations. The results indicate the existence of at least two rotamers of the bithiophene radical cation. The time-domain method was applied to the simultaneous fitting of the absorption and resonance Raman spectra.